2019
DOI: 10.3390/nu11102518
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Metabolic Flexibility and Hunger Hormone Ghrelin Exist between FTO Gene Variants in Response to an Acute Dietary Challenge

Abstract: The rs9939609 polymorphism of the fat mass and obesity-associated (FTO) gene has been associated with obesity, and studies have also shown that environmental/lifestyle interaction such as dietary intake might mediate this effect. The current study investigates the postprandial hormonal regulators of hunger and indirect markers of substrate utilisation and metabolic flexibility following a dietary challenge to determine if suppression of circulating ghrelin levels and/or reduced metabolic flexibility exist betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In this study related to the rs9939609 T>A on FTO gene and appetite traits in normal weight participants, we found a higher intake of added sugars in carriers of the TA + AA genotypes versus the TT genotype. This finding coincides with other studies in which a higher intake of carbohydrates has been reported, but the classification of the type of carbohydrates was not described [17, 41]. Nevertheless, the study of Brunkwall et al [19] found a higher consumption of pastry and bakery products in carriers of the A allele, which would coincide with what was reported in our study since these foods are characterized by a high content of added sugars.…”
Section: Discussionsupporting
confidence: 92%
“…In this study related to the rs9939609 T>A on FTO gene and appetite traits in normal weight participants, we found a higher intake of added sugars in carriers of the TA + AA genotypes versus the TT genotype. This finding coincides with other studies in which a higher intake of carbohydrates has been reported, but the classification of the type of carbohydrates was not described [17, 41]. Nevertheless, the study of Brunkwall et al [19] found a higher consumption of pastry and bakery products in carriers of the A allele, which would coincide with what was reported in our study since these foods are characterized by a high content of added sugars.…”
Section: Discussionsupporting
confidence: 92%
“…FTO (rs9939609), GHRL (rs34911341), LEPR (rs1137101), polymorphisms which affect the amount of food consumed and the feeling of satiety [ 49 , 50 , 51 , 52 , 53 , 54 , 55 ];…”
Section: Resultsmentioning
confidence: 99%
“…Magno et al, studying the FTO rs9939609 polymorphism, showed that the subject with AA genotype indeed had decreased postprandial ghrelin concentration [46]. In contrast, Danaher et al did not confirm the relationship between the rs9939609 polymorphism of the FTO gene and the preprandial or postprandial ghrelin level [81]. These various reports may highlight the complexity of the interaction mechanisms between FTO and ghrelin, but more research is needed to fully understand them.…”
Section: Fto and Gastrointestinal Tract Hormonesmentioning
confidence: 99%